Politics, personality and bureaucracy [review of] - Pacho, Arturo G. (1978)
A review of Donald P. Warwick with Marvin Meade and Theodore Reed, A Theory of Public Bureaudracy: Politics, Personality and Organization in the State Department (Cambridge, Mass.: Harvard University Press, 1975), 252 pp.
Keywords: Book reviews